Development Of Interactive Media With Edpuzzle In Improving Understanding Capability Mathematical Concepts - Herwindo, Rully; Noer, Sri Hastuti; Sutiarso, Sugeng (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
Based on the research results of 31 students who experienced difficulty in understanding mathematical concepts, by using Research and Development (R&D), and developing interactive media with Edpuzzle with the ADDIE model after experimental treatment, in learning some students experienced an increase in understanding of mathematical concepts, but the results of the analysis This results in an effectiveness of 0.89 with the effective criteria. After treatment was carried out through the development of interactive learning media with edpuzzle with validity of 80.73% with valid criteria, practicality of 81.0% with very practical criteria. The results of these values ​​indicate that the media questionnaire results are suitable for use. The results of this research state that the development of interactive media with edpuzzle can effectively improve students' understanding of mathematical concepts.